Blockchain-Enhanced Maritime Education Ecosystem: Decentralized Credentialing for Global Seafarer Competency Verification - Pargaulan Dwikora Simanjuntak; Ikhwanuddin; A. Nurfajri Irwan; Yayu Nopriani Martha; Giovanni Battista Puteri (Marasofi International Media and Publishing (MIMP), 2026)
The global maritime industry faces a critical seafarer shortage of 89,510 officers, exacerbated by fragmented credential verification systems, fraudulent certification practices, and inefficient competency recognition across jurisdictions. This research develops a comprehensive Blockchain-Enhanced Maritime Education Ecosystem integrating decentralized credentialing infrastructure with IoT-enabled simulation training and economic impact assessment of maritime labor market transformation. Through qualitative analysis incorporating perspectives from maritime education experts, certification authority administrators, and shipping company training managers, this study identifies critical requirements for trustless verification systems, interoperability standards, and stakeholder adoption barriers. The framework synthesizes educational technology innovations with maritime training regulatory compliance, demonstrating how blockchain-based credentialing can simultaneously enhance seafarer mobility, reduce certification fraud, and improve competency verification efficiency while addressing cybersecurity concerns and digital divide challenges. Findings reveal significant gaps in current certification systems, particularly regarding cross-jurisdictional recognition mechanisms and real-time competency tracking capabilities. The research contributes actionable implementation pathways for maritime stakeholders globally, offering evidence-based strategies for digital transformation of seafarer credentialing aligned with STCW Convention requirements and SDG 4 (Quality Education), while addressing the urgent workforce development needs essential for maritime industry sustainability and operational safety.